Pengaruh Variasi Lama Pengeringan Terhadap Karakteristik Mutu Produk Dendeng Ikan Lele Dumbo (Clarias Gariepinus) Setelah Penggorengan - Wiranto, Adi; Husain, Rahim; Mile, Lukman (Jambura Fish Processing Journal, 2024)
The study aimed at analyzing the influence of drying time variations on quality characteristics of jerked dumbo catfhis (clarias gariepinus) after being fried. Non-factorial Completely Randomized Design test, it was continued by ANOVA test. if ANOVA test result stated that it had siqnificance and very significant influence, it would be continued with Duncen Test. The next step was to determine the chosen product using Bayes method. After the chosen product was determined, it was continued with proximate test and TPC. The test result was analyzed applying IBM SPSS Statistic v.16. This study consisted of 3 treatments with two repetitions (7 hours drying time (A1), 8 hours drying time (A2), and 9 hours drying time (A3). The best drying time, according to Bayes test, was A2 (8 hours ) by having sensory organoleptic on parameter of color for 8,36, aroma for 8,36 taste for 8,36, and texture for 8,2, Then the chosen product contemed 39,63% water, 1,39% dust, 37,42 % protein, 2,46% fat, and 29,28% carbohydrate and total plate count was 1.87x103 or 3,27.